Moral Education and Pancasila in Encouraging the Prevention of Intolerance in the Era of Globalization: Experiences of Indonesia and Malaysia - Azhar Moeloek Akbar; Tsania Rahma; Yehezkiel Lemuel; Debby Fitriana; Tiara Rizki Annesha Fanani; Rosa De Lima Gita Sekarjati (Universitas Negeri Semarang, 2022)
Indonesia and Malaysia are two multicultural countries that have various cultures. This is due to the geographical location of Indonesia which is an archipelagic country that stretches from the western end of Sabang Island to the eastern end of Merauke Island. So in conditions like this, various tribes, customs, ethnic cultures and beliefs emerged in Indonesia. This diversity has both positive and negative impacts. The positive impact is that diversity can strengthen unity, but the negative impact is that it can lead to division. One of the problems that can cause the division of the Indonesian nation is the intolerant behavior of the people. Intolerant behavior often occurs in people's lives in various fields. The fields of politics, economics, religion, social and culture are always inseparable from intolerant attitudes, especially in the development of the flow of information in the current era of globalization. There are many cases that trigger inter-ethnic divisions that circulate in the mass media, especially social media. Therefore, a guide for the Indonesian people is needed to deal with the issue of division, namely Pancasila. Pancasila which is the nation's ideology has values ​​that become the view of life of the Indonesian people which are always relevant to the times, especially in the current era of globalization. By implementing and preserving Pancasila in all areas of people's lives, it means that we are trying to realize a common life that is conditional on the values ​​of unity, kinship, justice, tolerance and humanity.